World disorders : troubled peace in the post-Cold War era - Hoffmann, Stanley (Lanham, Md. : Rowman & Littlefield, 1998)
"Stanley Hoffmann has remarked that "it wasn't I who chose to study world politics. World politics forced themselves upon me." A rootless child of World War II, Austrian, French, and later American, he has always maintained a unique balance and perspective on global affairs. Hoffmann brings together in this volume his important recent work on international politics. Many published here for the first time, these essays offer incisive reflections upon the reemergence of nationalism and ethnic conflicts in Europe, the redefined role of military intervention, and other uncertainties brought on by the demise of the Cold War. Hoffmann weighs the influence on theory and policy of such disparate figures as John Rawls, Hedley Bull, and George Schultz."--BOOK JACKET.
1. Introduction: From This Century to the Next -- 2. Hedley Bull and His Contribution to International Relations -- 3. Ideal Worlds -- 4. Beyond Realism and Idealism in International Politics -- 5. The Crisis of Liberal Internationalism -- 6. What Should We Do in the World? -- 7. A New World and Its Troubles -- 8. Delusions of World Order -- 9. The Price of War -- 10. In Defense of Mother Teresa -- 11. The Politics and Ethics of Military Intervention -- 12. Thoughts on the UN at Fifty -- 13. The Passion of Modernity -- 14. Nationalism and World Order -- 15. On Ethnic Conflicts and Their Resolution -- 16. Nation and Nationalism in America Today -- 17. Conclusion: Principles of a Liberal Ethics for International Relations: A Normative Outline.
Includes bibliographical references (p. 255-268) and index.
Keywords: Peace; War; Security, International; International cooperation; International organization